3(z-2)+6=5(z+4z)

Simple and best practice solution for 3(z-2)+6=5(z+4z) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(z-2)+6=5(z+4z) equation:



3(z-2)+6=5(z+4z)
We move all terms to the left:
3(z-2)+6-(5(z+4z))=0
We add all the numbers together, and all the variables
3(z-2)-(5(+5z))+6=0
We multiply parentheses
3z-(5(+5z))-6+6=0
We calculate terms in parentheses: -(5(+5z)), so:
5(+5z)
We multiply parentheses
25z
Back to the equation:
-(25z)
We add all the numbers together, and all the variables
-22z=0
z=0/-22
z=0

See similar equations:

| p^2-4p+18=7p-6 | | 4x -7 -7x = -1 | | 293=24-w | | c+3+4c-13=90 | | 7y -3y -8 = -32 | | 4x+20=3x-50=180 | | 2m-5=5m-2 | | 16x=14.5x^2 | | 13x/10=2 | | 3/4c-1/4c=7 | | 1/4y=5× | | h-18=-30 | | 7.7(x-2)=-0.3+48.6 | | X-8/3x=(-10) | | 3/5p+1/5{40-p}=0 | | 6+3x+2=8x | | 0=-16(X)+1/2*29*(x)^2 | | 5z^2+17z+13=0 | | -3=4x+18 | | 5x+17+6x+7=180 | | -0.74+0.54x=5.2 | | 0=-16(X)=1/2*29*(x)^2 | | 8/3m=-24 | | 0=2z-2z | | -0.53x+0.33x=6.2 | | 5=7(4+3a) | | 7x-(3x+5)-8=(8x+20)-7x+5 | | 16(k+5)-66=2(8k+7) | | 7x+2=-122 | | 11x+5=10x+21 | | 9(8-7k)+59k+4k=3 | | 6=9(2w+8)+5 |

Equations solver categories